The Young Generation with Integrity as the Encouragement of Anti-Corruption Character Education (Journal of Creativity Student, 2022)
Indonesia and corruption are two things that cannot be separated. Indonesia is very synonymous with the problem of corruption and vice versa, corruption is identical with Indonesia. This is undeniable considering the number of corruption cases in Indonesia that seem to be lost and lost. Nevertheless, the fight against corruption as a common enemy has not been carried out by the entire community. In this article, the author uses a normative research method based on primary and secondary data. The results of the analysis obtained are that character building is very important for the future successors of the Indonesian state because in the future they will be the ones who will lead the direction of the fate of the nation's life. With the participation of technology and modernization in various fields will grow a new hegemony.